Using didactic enclosures as teaching methods and social forms for active learning in chemical education - Sikošek, Darinka (Revija za elementarno izobraževanje, 2008)
Innovative teaching and learning can be defined as the effective use of various didactic materials combined with the methods and social forms of active learning. We carried out an evaluation of didactic enclosures as the initial stage in the methodology of our scientific strategy for researching the project "Didactic Redevelopment of Chemical Education in Slovenian Elementary Education". To obtain the results of our evaluation of didactic enclosures we concentrated on the innovative approach of using enclosures for just games and video. These types of enclosures are used in didactic game methods and video methods, as well as various problem-solving sheets (individual and group) that are typically used for individualised group work. We put special emphasis on furthering the development of programmed sequences, which are essential in effectively utilizing the wellknown teaching aid called the "Periodic Table in Cube".
Keywords: metodika; učne metode; didaktične igre; skupinsko delo; chemistry; kemija; osnovne šole